The Thin Red Line - Geisler, Robert Michael; Roberdeau, John; Hill, Grant; Malick, Terrence; A Geisler. Roberdeau ([S.l.] : Twentieth Century Fox, 1998)
Realistic view of military and moral chaos in the Pacific during World War II
Based upon the novel by James Jones
Edited by Billy Weber, Leslie Jones & Saar Klein ; screenplay, Terrence Malick
Cast : Sean Penn (1st Sgt. Welsh), Adrien Brody (Cpl. Fife), Jared Leto (2nd Lt. Whyte), Nick Nolte (Lt. Col. Tall)
Keywords: World War, 1939-1945 -- Motion pictures and the war; Guadalcanal, Battle of, Solomon Islands, 1942-1943 -- Drama; War films